Vibrational behavior of isotropic plate structures in contact with a bounded fluid via unified formulation - Canales, FG (2019)
This paper presents an analytical solution for free vibration analysis of thick rectangular isotropic plates coupled with a bounded fluid for various boundary conditions. In order to consider displacement theories of an arbitrary order, the Carrera Unified Formulation (CUF) is used. The eigenvalue problem is obtained by using the energy functional, considering plate and fluid kinetic energies as well as the potential energy of the plate. The Ritz method is used to evaluate the displacement variables, and the functions used in the Ritz series can be adjusted to consider any of the classical boundary conditions. The convergence of the solution is analyzed, and a validation of results considering open literature and 3D finite element software is performed. Parametric studies are carried out to obtain natural frequencies as a function of the side-to-thickness ratio, plate aspect ratio, fluid domain size, plate boundary conditions, and fluid-solid density ratio. Pressure and velocity in the fluid domain are evaluated in order to establish the consistency of the solution. Accurate results for thick plates are obtained with a much lower computational cost compared to that of 3D finite element solutions.